Multi user-based patient service information system in public health center - Wiendara G.C.; Abadi S.; Ilayaraja M.; Shankar K.; Nguyen P.T.; Hashim W.; Maseleno A. (Blue Eyes Intelligence Engineering and Sciences Publication, 2023)
The patient service information system at the Gisting Public Health Center, Bahasa: Pusat Kesehatan Masyarakat (Puskesmas), is the development of an existing and computerized drug inventory system. The patient service system existing at the Gisting Public Health Center does not support the recording of data so the data recording is not well organized. The purpose of this study is to create an application and implementation of a multiuser-based patient service information system. This system will provide the result of report and information needed by the patient services administration. It is hoped that this system can be used as an experienced assistant. This application helps in making decisions and operational activities as an effort to achieve the goals to be achieved by the Public Health Center. This application system analyzes the service data at the Gisting Public Health Center. This information system application development used Visual Basic 6.0 programming and for database used SQL Server 2000. BEIESP.